CONFLICT OF INTEREST DAN INDEPENDENSI AUDITOR PADA KANTOR AKUNTAN PUBLIK DI BALI - Komang Adi Kurniawan Saputra; Ni Made Rai Juniariani; A. A. Ketut Jayawarsa (Universitas Trunojoyo Madura, 2019)
This study aims to examine the effect of conflict of interest and independence on auditor performance at the Public Accounting Firm in Bali with quantitative research methods. The population in this study were auditors registered in the directory of the Institute of Public Accountants in Bali amounting to 67 auditors, which at the same time made the whole population sampled or called total sampling. The sampling technique used is a non-probability sampling method with saturated samples or census techniques. To test the influence between variables, OLS (Ordinary Least Square) Multiple Linear Regression is used. The results of this study are the conflict of interest variables and independence have a significant positive effect on the performance of the aduitor registered at the Public Accounting Firm in Bali.